2010
DOI: 10.3758/s13414-010-0036-z
|View full text |Cite
|
Sign up to set email alerts
|

Contrast and assimilation in categorization and exemplar production

Abstract: We studied contrast and assimilation in three tasks: an exemplar-production task, a categorization task, and a combined categorization-then-production task. On each trial of the first task, subjects produced a circle when prompted with a category label. In the second task, they classified lines that differed in length into one of four categories. On each trial of the combined task, they classified two lines and then produced a line when prompted by a category label. All three tasks converged on the same conclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
22
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 36 publications
3
22
0
Order By: Relevance
“…We probed this issue by using sequential effects. Recently, there has been a resurgence of interest in sequential effects, particularly during binary categorization processing (Hampton, Estes, & Simmons, 2005;Stewart, Brown, & Chater, 2002;Zotov, Jones, & Mewhort, 2011). In these studies, when a sequence of stimuli is presented, the categorization responses to the stimuli in current trials have been found to vary according to the local sequential context shaped by the immediately preceding stimuli presented one trial back.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We probed this issue by using sequential effects. Recently, there has been a resurgence of interest in sequential effects, particularly during binary categorization processing (Hampton, Estes, & Simmons, 2005;Stewart, Brown, & Chater, 2002;Zotov, Jones, & Mewhort, 2011). In these studies, when a sequence of stimuli is presented, the categorization responses to the stimuli in current trials have been found to vary according to the local sequential context shaped by the immediately preceding stimuli presented one trial back.…”
Section: Introductionmentioning
confidence: 99%
“…One interpretation suggests that sequential effects involve the computation of similarity/dissimilarity between preceding and current stimuli to guide perceptual judgments (Stewart & Brown, 2005;Stewart, et al, 2002). An alternative interpretation argues that sequential effects reflect the consequences regarding how the local sequential context shifts participants' internal criteria to the current category representation (Hampton, et al, 2005;Zotov, et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Contrast is the opposite effect, when the judgment of stimulus n moves farther away on the measurement scale from the judgment of stimulus nk. In this sense, assimilation can be thought of as an attracting force from the preceding stimulus, whereas contrast can be thought of as a repelling force (Zotov, Jones, & Mewhort, 2011).…”
mentioning
confidence: 99%
“…A contrast effect occurs when the difference in perception between, for example, two stimulus categories is increased rather than decreased when they are presented closely in time or simultaneously. Both contrast effects and assimilation effects have been observed, for example, in judgements of physical attractiveness [12], categorization and exemplar production [47], and the visual perception of natural scenes [28].…”
Section: Assimilation Effectsmentioning
confidence: 99%